2000
DOI: 10.1046/j.1469-0691.2000.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic characterization of Pseudomonas aeruginosa in patients with cystic fibrosis

Abstract: Typing with PFGE is well suited for detailed investigations of colonization with Pseudomonas aeruginosa in cystic fibrosis patients. Pyocin typing can provide additional information for epidemiologic purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 21 publications
1
35
0
3
Order By: Relevance
“…Stored isolates from the 100 patients were subject to molecular typing by PFGE, performed by a scientist blinded to clinical status, using the methods previously described by SPENCKER et al [4]. Plugs were digested with the restriction enzyme SpeI and electrophoresis was performed with a clamped homogenous electric fields-DRIII module (Bio-Rad Laboratories, Hercules, CA, USA) with modification of the switch times.…”
Section: Microbiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Stored isolates from the 100 patients were subject to molecular typing by PFGE, performed by a scientist blinded to clinical status, using the methods previously described by SPENCKER et al [4]. Plugs were digested with the restriction enzyme SpeI and electrophoresis was performed with a clamped homogenous electric fields-DRIII module (Bio-Rad Laboratories, Hercules, CA, USA) with modification of the switch times.…”
Section: Microbiologymentioning
confidence: 99%
“…Once established in the CF lung, P. aeruginosa is virtually impossible to eradicate. Although the age of P. aeruginosa acquisition is an important determinant of prognosis [2], transmission from one patient to another is historically thought to be an uncommon occurrence [3,4] and, accordingly, segregation based on infection status is not routine.…”
mentioning
confidence: 99%
“…Five colonies per patient were typed. PFGE of SpeI-genomic DNA digests of P. aeruginosa isolates was also performed [28].…”
mentioning
confidence: 99%
“…P. aeruginosa is widely distributed in the natural environment Aoi et al, 2000 , which increases the risk of it contaminating water dispensers. However, this bacterium is a pathogen associated with opportunistic infections Edamoto et al, 2009 , requiring special attention with respect to the potential for healthcare-associated infections Spencker et al, 2000 . Furthermore, Ralstonia pickettii Woo et al, 2002 and R. insidiosa Van der beek et al, 2005 , which exhibited the highest isolation rates observed in this study, also include species that may influence health. These bacteria are widely distributed in the natural world, including in water, soil and plants.…”
Section: Proposed Using a C E T I C A C I D O R H Y D R O G E N P E Rmentioning
confidence: 61%